Association between polymorphism of MMP-1 promoter and the susceptibility to anterior disc displacement and temporomandibular joint osteoarthritis. Issue 11 (November 2015) - Luo, Shufang; Deng, Mohong; Long, Xing; Li, Jian; Xu, Liqin; Fang, Wei
Highlights Some cases are vulnerable to anterior disc displacement without reduction (ADDWOR), even to osteoarthritis (OA). These susceptible cases may have different genetic background. The rs1799750 polymorphism is associated with the susceptibility of ADDWOR with or without OA.